2017
DOI: 10.1177/1073191117733547
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Profile of Intellectually Gifted Adults: Analyzing the Wechsler Adult Intelligence Scale

Abstract: The Wechsler Adult Intelligence Scale (WAIS) has been used extensively to study intellectual abilities of special groups. Here, we report the results of an intellectually gifted group on the WAIS-IV. Gifted individuals are people who obtained scores equal to or greater than 2 standard deviations above the mean on an intelligence test. Hence, the current study aims first, to examine mean group performance data of gifted individuals on the WAIS-IV; second, to revalidate the pattern of performance identified in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 70 publications
1
8
0
2
Order By: Relevance
“…The HIQ group reported, as expected in hypothesis 1, higher crisis of meaning and lower self-control than the HAA group. These results are in line with findings of scholars who suggested existential troubles [14,23], lower psychosocial adjustment among the HIQ [25][26][27][28][29], and group differences between HIQ and HAA [14,23].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The HIQ group reported, as expected in hypothesis 1, higher crisis of meaning and lower self-control than the HAA group. These results are in line with findings of scholars who suggested existential troubles [14,23], lower psychosocial adjustment among the HIQ [25][26][27][28][29], and group differences between HIQ and HAA [14,23].…”
Section: Discussionsupporting
confidence: 91%
“…This is particularly alarming when considering that intellectually gifted adults' meaning in life predicted their subjective well-being in a longitudinal study [24]. A broad body of studies with intellectually gifted persons suggests a similar tendency for psychosocial issues, such as a vulnerability for affective disorders and immune-related diseases [25], identity problems, compulsivity [26], a low sense of coherence [27], a fearful attachment style [28], and the perception of being different [29].…”
Section: Introductionmentioning
confidence: 99%
“…First, it provided a developmental perspective to better understand the cognitive growth of gifted individuals. The gifted display precocious and advanced cognitive development in perceptual reasoning, abstract thinking, and conscious awareness, which influences their future academic performance, motivation for learning and self-development, and commitment in specific interest domains (Jung & Worrell, 2017;Lang, Matta, Parolin, Morrone, & Pezzuti, 2017;Silverman, 2018). Furthermore, this review reveals that although gifted children reach the Piagetian stages earlier and move through them at an accelerated pace, the association between IQ and Piagetian tasks becomes more important as children mature (Berninger & Yates, 1993).…”
Section: Discussion About Cognitive and Psychological Development Of Gifted Childrenmentioning
confidence: 91%
“…However, despite the fact that some studies considering the results of traditional IQ testing have reported that the gifted display better performance in the domains of working memory (WM) and speed of processing (SP) than typically developing children, findings remain mixed. In fact, it has been suggested that the gifted display a weakness with regard to solving SP tasks speedily (Lang, Matta, Parolin, Morrone, & Pezzuti, 2017). Taken together, these results demonstrate that gifted children perceive an unusual quantity of information from the environment as a result of heightened sensory awareness, suggesting a link between giftedness and perceptual superiority (Hindal, 2014), which may be one of the factors leading to recognizing as gifted those children with a visual-spatial approach to thinking (Silverman, 2000).…”
Section: Theme I: Cognitive Development Of Gifted Childrenmentioning
confidence: 99%
“…On the one hand, regarding the male gender being more prevalent, research shows a greater number of male students, one of the possible hypotheses for this phenomenon being a view historically permeated by prejudices, mainly related to the education of women (Gontijo, 2007;Lang, Matta , Parolin, Morrone, & Pezzuti, 2017;Tentes & Fleith, 2014). On the other hand, Pedro et al (2016) state that, for social reasons, the experience of giftedness in women is given differently, since cultural values regarding intelligence need to be considered and questioned.…”
Section: Discussionmentioning
confidence: 99%